2021
DOI: 10.1177/11795476211043067
|View full text |Cite
|
Sign up to set email alerts
|

Non-Operative Management of Bronchobiliary Fistula Due to Proximal Migration of Biliary Stent in a Patient With Unresectable Klatskin Tumor

Abstract: Introduction: One of the methods for the biliary tree decompression in the case of Klatskin tumor is transpapillary stenting, which could be completed by stent migration in 4% to 10% of cases. Approximately half of the stent migrations are in the proximal direction. In this study, we reported a rare case of proximal trans-diaphragmatic stent migration to the lower lobe of the right lung with the formation of a biliary-bronchial fistula (BBF). Case presentation: A 60-year-old woman was diagnosed with hilar chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…Previous studies [ 11 , 23 , 24 ] have found that the incidence of biliary fistula after such surgery is high, and biliary fistula has adverse effects on the short-term and long-term prognosis of patients. In this study, the incidence of biliary fistula after radical resection of hilar cholangiocarcinoma was 20.63%, which was lower than that reported in the previous literatures [ 12 , 25 , 26 ]. The reason may be that they have reported biliary fistulas with grades A, B, and C at the same time, and we only reported grade B, C cases of biliary fistula.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Previous studies [ 11 , 23 , 24 ] have found that the incidence of biliary fistula after such surgery is high, and biliary fistula has adverse effects on the short-term and long-term prognosis of patients. In this study, the incidence of biliary fistula after radical resection of hilar cholangiocarcinoma was 20.63%, which was lower than that reported in the previous literatures [ 12 , 25 , 26 ]. The reason may be that they have reported biliary fistulas with grades A, B, and C at the same time, and we only reported grade B, C cases of biliary fistula.…”
Section: Discussioncontrasting
confidence: 69%
“…In this study, preoperative cholangitis and positive Klebsiella pneumoniae in preoperative bile culture may be associated with the occurrence of postoperative clinically relevant biliary fistulas. Inflammation caused by biliary tract infection can lead to bile duct wall edema and the formation of small abscesses, hinder the healing of postoperative bile duct stumps and lead to the occurrence of hepatic section or anastomotic biliary leakage [ 25 , 34 ]. Previous studies [ 35 , 36 ] have shown that the clinical isolation rate and drug resistance rate of Klebsiella pneumonia e are increasing year by year, and it has become one of the main pathogens of biliary tract infection.…”
Section: Discussionmentioning
confidence: 99%
“…Extrahepatic stent migration is very rare, but bronchobiliary fistula, biliary pneumonitis, hepaticogastric fistula, pleural effusion, and abdominal wall abscess have been reported after stent migration through the liver capsule. [7][8][9][10][11] To the best of our knowledge, there are only 3 reported cases of stent migration involving the pericardium. [4][5][6] The first 2 published cases described patients with IgG-4associated cholangitis who presented with chest pain and echocardiogram changes after $10F stent placement.…”
Section: Discussionmentioning
confidence: 99%
“…Extrahepatic stent migration is very rare, but bronchobiliary fistula, biliary pneumonitis, hepaticogastric fistula, pleural effusion, and abdominal wall abscess have been reported after stent migration through the liver capsule. 7–11 To the best of our knowledge, there are only 3 reported cases of stent migration involving the pericardium. 4–6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation